Localized Intersections of Non-Extremal p-branes and S-branes - Edelstein Glaubach, José Daniel (2004)
A class of solutions to Supergravity in 10 or 11 dimensions is presented which extends the non-standard or semi-local intersections of Dp-branes to the case of non-extremal p-branes. The type of non-extremal solutions involved in the intersection is free and we provide two examples involving black-branes and/or D-\bar{D} systems. After a rotation among the time coordinate and a relatively transverse radial direction the solutions admit the interpretation of an intersection among D-branes and S-branes. We speculate on the relevance of these configurations both to study time dependent phenomena in the AdS/CFT correspondence as well as to construct cosmological brane-world scenarios within String Theory admitting accelerating expansion of the Universe.